Paul's 'new moment': the reception of Paul in Alain Badiou, Terry Eagleton, Slavoj Zizek - Cuff, SL (2014)
This thesis traces the ‘New Moment’ in Pauline reception in the writings of Alain Badiou, Terry Eagleton and Slavoj Žižek. It explores how the Pauline epistles are read and feature in their thought. An answer to the question, 'why Paul?' prompts reflection on what it is to read and understand the Apostle. An introduction sets out the writers of this ‘New Moment’ [Jacob Taubes, Giorgio Agamben, Stanislas Breton, as well as Badiou, Eagleton and Žižek] before isolating the figures of this study. The reception of this ‘moment’ by mainstream New Testament studies is considered, and with it the charge of ‘appropriation’. The concept of ‘appropriation’ is explored, and a definition arrived at, for the purpose of evaluating the readings we will go on to discover. As part of this notion of ‘appropriation’, the turn to Gadamer in recent New Testament study is surveyed. We suggest another potential hermeneutical approach that derives from Gadamer is possible. Thus, the object of this study is both an instance of, and means by which to critique the understanding of, New Testament Wirkungsgeschichte. Each of our thinkers is then considered in turn. The outline for each chapter is the same. A brief introduction to the figure with bibliographical background salient to his Pauline reading precedes some textual examples indicative of that reading. We then move to analyse the manner of that reading and certain conceptual problems which are revealed in the course of the engagement with Paul. The conclusion analyses the approaches, and reasons for turning, to Paul on the part of these thinkers. Salient differences between each thinker's reading are noted and the charge of appropriation is evaluated afresh. The implications of such readings for conventional biblical criticism are considered, and the success of an approach which explores a Gadamerean-inspired interest in reception in the manner adopted by this thesis is judged.